Object Classification Via Transferable Belief Model: Case-Based Approach - (:unkn) unknown (IEEE, 2020)
In this study, a belief function theory based supervised classifier that is able to determine the class of a ship automatically is developed Transferable belief model is used to model the uncertainty and impreciseness about the measurements obtained from sensors. The case-based classifier developed in the context of the transferable belief model is realized and its accuracy is measured on an artificial database.
Keywords: belief function theory; transferable belief model; object classification; COMBINATION; RULE